1999
DOI: 10.1046/j.1439-0523.1999.00382.x
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to powdery mildew in selections from Tunisian landraces of barley

Abstract: Two!hundred and thirty!two accessions of barley landraces collected from Tunisia were screened for resistance to powdery mildew[ A number of race!speci_c genes were detected using the detached leaf technique[ Among the 121 accessions tested\ 058 were susceptible to powdery mildew\ 19 were resistant and 32 showed di}erential reactions to the three isolates of powdery mildew used[ An attempt was made to deter! mine the number of genes\ the types of gene\ the types of gene action and the gene loci in 19 resistant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
22
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 33 publications
5
22
0
2
Order By: Relevance
“…Since 1930, when isolates of powdery mildew with different virulence genes were identified by Mains and Dietz (1930), specific isolates (usually 1 3 isolates) were used for screening collections of barley for genes for resistance (Jørgensen 1994, Czembor andJohnston 1999). However for a total number of about 280 000 of barley accessions (most of them landraces) which is estimated to exist world-wide in ex situ germplasm collections (Knüpffer and Hintum 1995) only less than 2 percent attempts have been made to identify powdery mildew resistance genes using differential lines and isolates (Czembor 1996(Czembor , 2001).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since 1930, when isolates of powdery mildew with different virulence genes were identified by Mains and Dietz (1930), specific isolates (usually 1 3 isolates) were used for screening collections of barley for genes for resistance (Jørgensen 1994, Czembor andJohnston 1999). However for a total number of about 280 000 of barley accessions (most of them landraces) which is estimated to exist world-wide in ex situ germplasm collections (Knüpffer and Hintum 1995) only less than 2 percent attempts have been made to identify powdery mildew resistance genes using differential lines and isolates (Czembor 1996(Czembor , 2001).…”
mentioning
confidence: 99%
“…Identification of powdery mildew resistance genes based on tests performed on seedlings using isolates with different virulence spectra is effective and sufficient for breeders and pathologist needs (Brückner 1964, Dreiseitl 1999, Dreiseitl and Jørgensen 2000. However, confirmation of putative resistance genes or alleles can only be established through the evaluation of progeny from crosses among appropriate genotypes (Jørgensen 1994, Czembor and Johnston 1999. Vavilov (1926) proposed that the region of Mediterranean Sea is major center of crop origin.…”
mentioning
confidence: 99%
“…This broad RS is not surprising in view of the landrace-derived origin of this line. Landraces have been used extensively within the primary gene pool of barley to mine both genes and alleles associated with disease resistance (Jørgensen and Jensen 1997;Czembor 1999;2001). Indeed, several powdery mildew resistance genes used commercially are derived from barley landraces (Fischbeck and Jahoor 1991).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the genes Mlg, Mlak, Mla7, and Mla(Ab) have also been detected in North American cultivars (Dreiseitl and Steffenson 2000). Likewise, the genes Mlg, Mlk, Mla7, MI(CP), and Mla1 were previously detected in a population of 108 Baltic spring barley cultivars and breeding lines (Tueryapina et al 1996), the genes Mla1, Mla7, and Mlk were detected in Tunisian landraces (Czembor and Johnston 1999), and the genes Mlg and Mla7 were detected in a population of 20 cultivars from Greece (Czembor and Bladenopoulos 2001). Based on these previous reports and on the present study, the most commonly found R-genes for powdery mildew in barley appear to be Mlg, which has been introduced into many European cultivars a long time ago, and Mla7, which has also been introduced into common barley varieties over the years.…”
mentioning
confidence: 94%
“…As a first step towards the effective use of powdery mildew R-genes in breeding programs, it is essential to test for the presence of those genes in registered cultivars and for the virulence of the pathogen through periodical surveys (Czembor and Bladenopoulos 2001;Czembor 1998, 2000a;Czembor and Gacek 1990;Czembor and Johnston 1999). In practice, such surveys are conducted based on the gene-for-gene hypothesis, i.e.…”
mentioning
confidence: 99%